2010
DOI: 10.4049/jimmunol.0902301
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Invariant NKT Cell Regulation of Allergic Airway Disease Is Dependent on IFN-γ Production

Abstract: Invariant NKT cells (iNKT cells) play a pivotal role in the development of allergen-induced airway hyperresponsiveness (AHR) and inflammation. However, it is unclear what role they play in the initiation (sensitization) phase as opposed to the effector (challenge) phase. The role of iNKT cells during sensitization was examined by determining the response of mice to intratracheal transfer of OVA-pulsed or OVA–α-galactosylceramide (OVA/αGalCer)-pulsed bone marrow-derived dendritic cells (BMDCs) prior to allergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 62 publications
(82 reference statements)
1
19
1
Order By: Relevance
“…Similarly, our study found that activated CD8 + T induced DCs with tolerogenicity through an IFN-c dependent manner in vitro. Interestingly, previous reports indicated that IFN-c could attenuate CD4 + T mediated airway inflammation by counteracting the Th2 response, remodeling invariant NKT cells, inhibiting eosinophil differentiation, and having direct effects on airway epithelium [46][47][48][49]. But, here we showed that CD8 + T activation in vivo, which resulted in a substantial secretion of IFN-c in BAL, could alleviate airway inflammation in OVA-induced asthma in CD8 + T deficient mice.…”
Section: Discussioncontrasting
confidence: 65%
“…Similarly, our study found that activated CD8 + T induced DCs with tolerogenicity through an IFN-c dependent manner in vitro. Interestingly, previous reports indicated that IFN-c could attenuate CD4 + T mediated airway inflammation by counteracting the Th2 response, remodeling invariant NKT cells, inhibiting eosinophil differentiation, and having direct effects on airway epithelium [46][47][48][49]. But, here we showed that CD8 + T activation in vivo, which resulted in a substantial secretion of IFN-c in BAL, could alleviate airway inflammation in OVA-induced asthma in CD8 + T deficient mice.…”
Section: Discussioncontrasting
confidence: 65%
“…As a consequence, the development of AHR in a murine model using OVA was blocked [70]. Another study demonstrated that transfer of bone marrow dendritic cells (BMDCs) treated with α-GalCer, prevented the development of lung allergic responses, and this was dependent on IFN-γ production by recipient type I NKT cells [71]. All these findings suggest novel therapeutic strategies for asthma by eliminating or skewing type I NKT cells toward Th1 functions.…”
Section: Allergic Asthmamentioning
confidence: 97%
“…IL-4 or IL-13 production from iNKT cells is required for the development of allergic asthma in mouse models, while iNKT cells can produce IFN-γ, which can suppress the Th2 response and thereby prevent allergic asthma. However, even when employing similar protocols, different institutes obtained completely different findings (33, 36, 37). Since iNKT cells can detect bacterial components through their invariant TCRs or Toll-like receptors, the difference in the lung microbiota may affect the function of distinct iNKT cell subsets, such as NKT1 and NKT2.…”
Section: Beneficial and Detrimental Effects Of Inkt Cells For Allergimentioning
confidence: 99%
“…Moreover, a protective role of iNKT cells in allergic asthma was suggested. Subsequent AHR in these models can be suppressed by the systemic activation of iNKT cells by α-GalCer treatment or the transfer of α-GalCer-loaded bone marrow-derived DCs before OVA challenge in an IFN-γ-dependent manner (36, 37). In addition, Grela et al reported that IFN-γ-producing iNKT cells stimulated with toll like receptor (TLR) 7 agonist (R848) attenuated allergic asthma, which is consistent with the finding that TLR7 stimulation not only enhances viral responses but also alleviates experimental asthma (38).…”
Section: Beneficial and Detrimental Effects Of Inkt Cells For Allergimentioning
confidence: 99%